Osseointegration Aspects of Implants at the Bone Reconstruction Site by a Novel Porous Titanium Scaffold - Kazuya Doi; Reiko Kobatake; Yusuke Makihara; Yoshifumi Oki; Hanako Umehara; Takayasu Kubo; Kazuhiro Tsuga (Stilus Optimus, 2021)
Objectives: Porous titanium is used for the reconstruction of large bone defects due to its excellent mechanical strength. The quality of osseointegration of implants placed in bone reconstructed with porous titanium is unknown. The purpose of this in vivo study was to evaluate the osseointegration of implants at sites reconstructed using porous titanium. Material and Methods: Hollow porous titanium (Ti) (outer-diameter 6 mm, inner-diameter 2 mm, length 4 mm, 85% porosity) and similar-sized porous hydroxyapatite (porous HA: 75% porosity) samples were prepared and implanted in 6 New Zealand white rabbit femurs. Four weeks later, an implant bed was created to receive a Ti implant (diameter 2 mm, length 4 mm). An implant placed at a pristine bone site served as the control. Four weeks later, histological and histomorphometric evaluations of the test and control sites were conducted. Results: Osseointegration was observed in all groups. There was no significant difference in the bone formation ratio and bone-implant contact (BIC) ratio across all groups for the whole area. At the cancellous bone area of the bone defect, superior bone formation ratio and BIC ratio were observed with porous Ti and porous HA compared to the control (bone formation ratio: control 1.8 [SD 3]%, HA 23 [SD 3]%, Ti 23.6 [SD 5]%; BIC ratio: control 5.4 [SD 5.3]%, HA 28.9 [SD 10.7]%, Ti 41.6 [SD 14]%). Porous Ti demonstrated good osteoconduction and osseointegration abilities, similar to porous HA. Conclusions: To our knowledge, this is the first report of implant treatment after preliminary bone reconstruction using a titanium biomaterial. Porous titanium is a suitable material for bone reconstruction before implant treatment in load-bearing areas that allow subsequent prosthetic treatment.